The Impact Of The Digital Era On Achieving The Objectives Of The Islamic Economy - Muhammad Rabie Ahmad Hussain (International Conference on Islamic Economic (ICIE), 2023)
This research paper seeks to know the importance and impact of the digital era on achieving the objectives of the Islamic economy. By crystallizing the concept of the digital era, and examining whether this digital era is in line with the objectives of the Islamic economy. The research also deals with the study of the Islamic endowment model, and the extent of its development by following modern digital mechanisms. The research follows the descriptive and inductive approach, by tracing the major purposes and objectives of the Islamic economy, and then applying them to the subject of study.